The 1831 CE mystery eruption identified as Zavaritskii caldera, Simushir Island (Kurils) - Hutchison, William; Sugden, Patrick; Burke, Andrea; Abbott, Peter; Ponomareva, Vera V.; Dirksen, Oleg; Portnyagin, Maxim V.; MacInnes, Breanyn; Bourgeois, Joanne; Fitzhugh, Ben; Verkerk, Magali; Aubry, Thomas J.; et al. (Proceedings of the National Academy of Sciences, 2025)
Funding: W. Hutchison is funded by a UKRI Future Leaders Fellowship (MR/S033505/1). A. Burke is funded by a Philip Leverhulme prize in Earth Sciences (PLP-2021-167) from the Leverhulme Trust. P. Abbott and M. Sigl received funding from the European Research Council under the European Union’s Horizon 2020 research and innovation programme (grant agreement no. 820047). S. Davies acknowledges support from a Royal Society Leverhulme Trust Senior Fellowship. The St Andrews EPMA was supported by the EPSRC Light Element Analysis Facility Grant EP/T019298/1 and the EPSRC Strategic Equipment Resource Grant EP/R023751/1. Polar ice cores and historical records evidence a large-magnitude volcanic eruption in 1831 CE. This event was estimated to have injected ~13 Tg of sulfur (S) into the stratosphere which produced various atmospheric optical phenomena and led to Northern Hemisphere climate cooling of ~1 °C. The source of this volcanic event remains enigmatic, though one hypothesis has linked it to a modest phreatomagmatic eruption of Ferdinandea in the Strait of Sicily, which may have emitted additional S through magma–crust interactions with evaporite rocks. Here, we undertake a high-resolution multiproxy geochemical analysis of ice-core archives spanning the 1831 CE volcanic event. S isotopes confirm a major Northern Hemisphere stratospheric eruption but, importantly, rule out significant contributions from external evaporite S. In multiple ice cores, we identify cryptotephra layers of low K andesite-dacite glass shards occurring in summer 1831 CE and immediately prior to the stratospheric S fallout. This tephra matches the chemistry of the youngest Plinian eruption of Zavaritskii, a remote nested caldera on Simushir Island (Kurils). Radiocarbon ages confirm a recent (<300 y) eruption of Zavaritskii, and erupted volume estimates are consistent with a magnitude 5 to 6 event. The reconstructed radiative forcing of Zavaritskii (−2 ± 1 W m−2) is comparable to the 1991 CE Pinatubo eruption and can readily account for the ...